The secret garden - Burnett, Frances Hodgson, 1849-1924 (First Avenue Editions, a division of Lerner Publishing Group, 2014)
Ten-year-old orphan Mary Lennox comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden.